Penoscrotal fistula secondary to urethral diverticulum treated with ventral penile skin flap urethroplasty: A case report - Can Tuygun (Elsevier, 2022)
Voiding symptoms and penoscrotal mass with/without fistula are typical findings of urethral diverticulum. We present a case of 55-year-old male patient who was evaluated for voiding symptoms, soft palpable penoscrotal mass and fistula. Retrograde urethrography, scrotal ultrasonography and cystoscopy revealed a urethral diverticulum and fistula. The defect developed after excision of the diverticulum associated with the penile ventral urethra was closed with a penile skin flap. In the 6-month follow-up, the patient did not have any voiding complaints and no signs of recurrence. Urethroplasty using a penile skin flap may be preferred in the repair of penile ventral urethral defect.